Essai de typologie des espaces résidentiels à partir d’indicateurs désagrégés à l’échelle du bâtiment. Application à Besançon et à Metz - Yohan Sahraoui (Unité Mixte de Recherche 8504 Géographie-cités, 2014)
In France, knowledge about urban spaces can be assumed by typologies built from statistical information at the scale of municipalities or blocks (provided by the French national institute of statistics for example). Nevertheless, these typologies do not consider cities at the desegregated scale of their buildings and usually do not take into account the diversity of buildings’ residential neighborhood. But this diversity explains a part of people and household’s choices in terms of mobility and lifestyle. The aim of this paper is to create a classification based on desegregated data, in order to better qualify urban spaces. After a short theoretical review about urban unity or diversity (Part 1), Part 2 presents the 46 selected indicators at the scale of the immediate, nearby or global neighborhood of the buildings. Part 3 presents the results of the classification, based on data analysis (PCA and HAC), which allow statistical and graphical generalization of the two studied areas: Besançon and Metz. These results improve knowledge about the organization and the residential attributes of urban spaces.